2003
DOI: 10.1002/da.10080
|View full text |Cite
|
Sign up to set email alerts
|

Factorial validity of the center for epidemiologic studies-depression (CES-D) scale in military peacekeepers

Abstract: Despite widespread use of the Center for Epidemiologic Studies Depression Scale [CES-D], there are no investigations that examine its factor structure in a military sample. Separate confirmatory factor analyses were performed on responses to the CES-D obtained from 102 female and 102 male Canadian military peacekeepers in order to compare the fit of a four-factor intercorrelated (lower-order) model to a four-factor hierarchical (higher-order) model. The intercorrelated and hierarchical models fit the data well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 43 publications
0
24
1
Order By: Relevance
“…Objectively measured physical fitness data was obtained via the APFT, a three-event physical performance test used to assess physical fitness in three domains: (1) cardiorespiratory fitness, (2) upper body muscular fitness, and (3) abdominal/core muscular fitness (16). The APFT involved three timed events performed in sequential order: a push-up event (the number of repetitions completed in two minutes), a sit-ups event (the number of repetitions completed in two minutes), and lastly a timed two-mile run event.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Objectively measured physical fitness data was obtained via the APFT, a three-event physical performance test used to assess physical fitness in three domains: (1) cardiorespiratory fitness, (2) upper body muscular fitness, and (3) abdominal/core muscular fitness (16). The APFT involved three timed events performed in sequential order: a push-up event (the number of repetitions completed in two minutes), a sit-ups event (the number of repetitions completed in two minutes), and lastly a timed two-mile run event.…”
Section: Methodsmentioning
confidence: 99%
“…This self-report scale is designed to measure depressive symptoms in the general population (28) and has been validated for use in military populations (3). The range of possible scores is 0 to 60, with higher scores indicating a higher degree of depressive symptoms (28).…”
Section: Methodsmentioning
confidence: 99%
“…Different studies have also shown two to seven-factor structure (Boisvert et al, 2003). Spijker et al (2004) studied three ethnic groups, including Moroccan, Turk, and Dutch with an exploratory comparison by applying the CES-D scale factor structure.…”
Section: Introductionmentioning
confidence: 99%
“…First, the findings of this study support the findings of research by Zlotnick et al (2002), as the present research demonstrates that subthreshold PTSD is associated with psychological morbidity and is an indicator of impairment in peacekeepers to a lesser degree than full PTSD. Second, levels of impairment on Depression and Health Problems approached the levels for those peacekeepers with full PTSD, as was the case in Boisvert et al (2003), highlighting the importance of subthreshold PTSD as a meaningful indicator of psychiatric morbidity. Finally, although the overall findings lend support to the validity of the current diagnostic thresholds for full PTSD, they also indicate that subthreshold PTSD is a meaningful diagnosis, as subthreshold PTSD significantly impacts the affect and mental health of the peacekeeping veteran.…”
Section: Subthreshold Ptsdmentioning
confidence: 89%